2017
DOI: 10.1371/journal.pone.0185188
|View full text |Cite
|
Sign up to set email alerts
|

Devices and tasks involved in the objective assessment of standing dynamic balancing – A systematic literature review

Abstract: BackgroundStatic balancing assessment is often complemented with dynamic balancing tasks. Numerous dynamic balancing assessment methods have been developed in recent decades with their corresponding balancing devices and tasks.ObjectiveThe aim of this systematic literature review is to identify and categorize existing objective methods of standing dynamic balancing ability assessment with an emphasis on the balancing devices and tasks being used.Data SourcesThree major scientific literature databases (Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 74 publications
(168 reference statements)
1
51
0
2
Order By: Relevance
“…It is believed that motor coordination is a key factor for injury prevention, as the gains in intermuscular coordination for landing may potentially reduce the likelihood of lower limb injuries. Wobble boards are simple and low‐cost devices widely used to investigate and improve balance and postural control . Previous studies have shown that such devices can provide fast improvement in balance performance with a long‐term retention, ultimately reducing the risk of ankle sprains by up to 50% .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that motor coordination is a key factor for injury prevention, as the gains in intermuscular coordination for landing may potentially reduce the likelihood of lower limb injuries. Wobble boards are simple and low‐cost devices widely used to investigate and improve balance and postural control . Previous studies have shown that such devices can provide fast improvement in balance performance with a long‐term retention, ultimately reducing the risk of ankle sprains by up to 50% .…”
Section: Introductionmentioning
confidence: 99%
“…Despite of many publications on the problem of balancing of the human body standing position, this problem was not investigated in a full measure. Petro et al undertook a systematic literature review to identify and categorize existing objective methods of standing dynamic balancing ability assessment with an emphasis on the balancing devices and tasks [21]. Three major scientific literature databases (Science Direct, Web of Science, PLoS ONE) and additional sources were used.…”
Section: Discussionmentioning
confidence: 99%
“…Other age-related factors such as attention switching delays and cognitive decline, may also explain the significantly lower gains and larger phase-shifts in the older than the young adults, especially in the unpredictable tracking tasks (Cofré Lizama et al, 2013;Cofré Lizama et al, 2014). Few studies have used surface perturbations to assess balance control in older adults and most of them have used discrete and not continuous perturbations as in the mechanical MELBA (Petro et al, 2017). Furthermore, few studies have used tracking tasks, mechanical or visual, to determine age-related balance changes (Arvin et al, 2016;Cofré Lizama et al, 2014;Sotirakis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%